Distinct pathways of mannan-binding lectin (MBL)- and C1-complex autoactivation revealed by reconstitution of MBL with recombinant MBL-associated serine protease-2. - Vorup-Jensen, T; Petersen, S; Hansen, A; Poulsen, K; Schwaeble, W; Sim, R; Reid, K; Davis, S; Thiel, S; Jensenius, J (2000)
Mannan-binding lectin (MBL) plays a pivotal role in innate immunity by activating complement after binding carbohydrate moieties on pathogenic bacteria and viruses. Structural similarities shared by MBL and C1 complexes and by the MBL- and C1q-associated serine proteases, MBL-associated serine protease (MASP)-1 and MASP-2, and C1r and C1s, respectively, have led to the expectation that the pathways of complement activation by MBL and C1 complexes are likely to be very similar. We have expressed rMASP-2 and show that, whereas C1 complex autoactivation proceeds via a two-step mechanism requiring proteolytic activation of both C1r and C1s, reconstitution with MASP-2 alone is sufficient for complement activation by MBL. The results suggest that the catalytic activities of MASP-2 split between the two proteases of the C1 complex during the course of vertebrate complement evolution.